IMPLEMENTASI METODE AGILE PADA RANCANG BANGUN SISTEM INFORMASI CAREER DEVELOPMENT CENTER PERGURUAN TINGGI - I Made Dwi Ardiada; Agus Tommy Adi Prawira Kusuma; Raden Agus Sarwa Edy; I Gede Pramana Ade Saputra (IDEALIS : InDonEsiA journaL Information System, 2025)
Higher education institutions in the digital era are faced the challenge of providing effective and efficient career services for their students. The current problem is the process of providing information on job vacancies in universities which is still posted in paper form and placed on glass walls. Apart from that, there are still many universities that do not have online information services to support careers for graduating students, one of which is the Career Center Service. On the partner side (agencies/industry) which require human resources, they still conventionally provide career information to universities in paper form which requires a glass wall to display the information so that it can be read by visitors who need the information. This research aims to design a university Career Development Center (CDC) Information System by implementing the Agile Method to overcome this problem. With the Agile method, the CDC information system design process in university becomes more effective and efficient. The stages of the Agile method are planning, Design, Testing, implementation, Review and Launch. The results obtained in this research are the CDC information system with 3 level access rights, namely student affairs, partners (company/industry agencies), and alumni/visitors. This research aims to create a CDC information system that can help universities have online services related to the Development of students who have graduated in obtaining job vacancy information flexibly, besides that students who have graduated and partners (agencies/industry) can online access information/provide vacancy information without the need to submit vacancy information papers to universities.